Citizenship : a very short introduction - Bellamy, Richard (Richard Paul) (Oxford ; New York : Oxford University Press, 2008)
Interest in citizenship has never been higher. But what does it mean to be a citizen in a modern, complex community? Richard Bellamy approaches the subject of citizenship from a political perspective and, in clear and accessible language, addresses the complexities behind this highly topical issue.
What is citizenship, and why does it matter? -- Theories of citizenship and their history -- Membership and belonging -- Rights and the 'right to have rights' -- Participation and democracy.
Includes bibliographical references (pages 124-128) and index.
Includes bibliographical references and index.
Keywords: Geschichte; Citizenship; Citoyenneté; 89.57 political participation; Citizenship; Citizenship; Citizenship; Citizenship